Release of geogenic fluoride from contaminated soils of Rajasthan, India: experiments and geochemical modeling - Thakur, Bhawna; Loganathan, Vijay A.; Sharma, Anupma; Sharma, Rakesh K.; Parker, Alison (Elsevier, 2023)
Management of groundwater contaminants, that are primarily of geogenic origin, such as fluoride, is a major public health concern. Worldwide, around 200 million people are dependent on drinking water resources that contain elevated levels of fluoride that exceeds WHO’s drinking water threshold limit of 1.5 mg/L. According to the Ministry of Drinking Water and Sanitation of India, about 11.7 million people, mostly in the Rajasthan state, are exposed to high fluoride risk. It is important to understand the soil–water interaction mechanisms to properly assess the fluoride contamination that are primrily due to geogenic origins prevalent in the region. In this study, batch desorption experiments were performed with soils obtained from varied depths at two sites in Rajasthan that has high fluoride levels in groundwater. The fluoride release kinetics followed a pseudo first-order kinetic model. The results of the batch experiments indicate higher release of fluoride from lower soil layers when compared to the upper layers. Further, the release of fluoride was dependent on pH wherein higher release was noticed under basic pH. Since the natural pH of the soils from this region is ca. pH 8 it is expected to play a vital role in the continued release of fluoride to the groundwater system. Furthermore, a simplified geochemical model, incorporating a general composite approach, has been used to simulate the experimental results that include dissolved Al and Al-F surface complexes. The model was able to capture the observed experimental results for various soils within a reasonable RMSE of 11.74%. The results of this study not only further the current understanding of the fate and transport mechanisms of fluoride in the contaminated subsurface but also would aid in designing remedial strategies to ensure future water security in this region.
Keywords: Fluoride pollution; Desorption kinetics; Geochemical modeling; Surface complexation; Rajasthan